2013
DOI: 10.1083/jcb.201212020
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing revised: A novel reepithelialization mechanism revealed by in vitro and in silico models

Abstract: Experimental analysis and computational modeling of epidermal wound closure in 3D suggests an important role for surrounding tissue in determining epithelial cell movement and fate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 71 publications
9
91
1
3
Order By: Relevance
“…19,20 However, our model provides a more biologically relevant context to study epithelial migration as a sheet and enables us to examine the support of this process by DFU-derived fibroblasts. 29 We found that incorporation of DFU-derived fibroblasts into this model recapitulated the impaired wound closure of DFUs. As we have previously shown that fibroblast-keratinocyte cross-talk directs re-epithelialization in this model, 12,28 our results further substantiate that DFU-derived fibroblasts have altered communication with keratinocytes.…”
Section: D In Vitro Chronic Wound Modelsmentioning
confidence: 86%
See 1 more Smart Citation
“…19,20 However, our model provides a more biologically relevant context to study epithelial migration as a sheet and enables us to examine the support of this process by DFU-derived fibroblasts. 29 We found that incorporation of DFU-derived fibroblasts into this model recapitulated the impaired wound closure of DFUs. As we have previously shown that fibroblast-keratinocyte cross-talk directs re-epithelialization in this model, 12,28 our results further substantiate that DFU-derived fibroblasts have altered communication with keratinocytes.…”
Section: D In Vitro Chronic Wound Modelsmentioning
confidence: 86%
“…*p < 0.05. To determine the ability of fibroblasts to support wound re-epithelialization Re-epithelialization NHKs, HFFs, DFUF/DFF/NFF 12,28,29 Self-assembled ECM Figure 5 To evaluate fibroblast capacity to synthesize and assemble ECM de novo…”
Section: Discussionmentioning
confidence: 99%
“…In the proliferation phase of the wound healing process, angiogenesis, collagen deposition, granulation tissue formation, re-epithelialization and wound contraction occur (Midwood et al 2004;Safferling et al 2013). Re-epithelialization of the epithelium occurs by proliferation and migration of epithelial cells atop of the wound bed providing cover for the new tissue (Safferling et al 2013). In this study, the proliferation and migration of oral mucosal cells treated with Pluchea indica extract and NPs containing Pluchea indica leaf extract were assessed to investigate the in vitro wound healing properties.…”
Section: Discussionmentioning
confidence: 99%
“…These cells alter their keratin expression profiles, increase their metabolic activities, and collectively form a thickened epithelial front that traverses a bed of provisional matrix beneath the scab. 3,4 Numerous paracrine interactions between keratinocytes, fibroblasts and immune cells promote re-epithelialization, while intercellular signals such as FGF, HGF, TGF-b and EGF family members likely play key modulatory roles. 5,6 After the wound has resolved, most of the suprabasal acanthotic layers of the regenerated epithelium are lost as the skin gradually reverts to a more normal, IFE-like phenotype.…”
Section: Introductionmentioning
confidence: 99%